Occluded object detection for autonomous vehicles employing YOLOv5, YOLOX and Faster R-CNN - Mostafa, Tanzim; Chowdhury, Sartaj Jamal (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.